Challenges in assessing the clinical utility and economic value of immune checkpoint inhibitor therapies of Cancer. Issue 1 (3rd September 2019) - Yu, Peter Paul; Eton, Omar; Garrison, Louis P.
Abstract : Advances in the immunotherapy of cancer have prolonged survival for cancer patients, but the clinical and financial impact of treatments must be considered in determining the overall clinical utility and economic value of therapeutic agents. Quality-adjusted life years and incremental cost-effectiveness ratios are clinical and economic metrics that can be used to evaluate the value of immune checkpoint inhibitors. This Commentary provides perspective on the limitations, benefits, and potential enhancement of this approach to support value-based medicine.